Ultrasound-Promoted Synthesis of 3,4-Dihydropyrimidin-2-(1H)-thiones via One-Pot, Three-Component Reaction Catalyzed by Formic Acid - A. Al-Alshaikh, Monirah (Asian Journal of Chemistry, 2011)
A simple method for the one-pot, three-component Biginelli condensation reaction of substituted aromatic aldehydes, b-ketoester and thiourea is described, employing anhydrous formic acid as an efficient catalyst using ultrasound irradiation method. Currently, ultrasound irradiation is applied in many fields of organic synthesis to shorten reaction times and easier workup matching with green chemistry protocols.